IMPROVING THE ORGANIZATION OF PRODUCTION CYCLES BY COTTON AND TEXTILE CLUSTERS IN THE ANDIJAN REGION (Scientific journal of the Fergana State University, 2024)
In this article, the state of the organization of production cycles in cotton-textile clusters in the Andijan region is covered and its causes are studied. The result is the problems of cotton-textile clusters in the region and their solutions